1996
DOI: 10.1107/s0108767396005934
|View full text |Cite
|
Sign up to set email alerts
|

Combination Rule of Σ Values at Triple Junctions in Cubic Polycrystals

Abstract: In cubic polycrystals, combinations of coincidence orientation relationships at a triple junction of grains A, B and C can be obtained by using the equationwhere d is a common divisor of 17AB and 17BC-This paper describes the derivation of this equation and shows several models of polycrystals composed of specially selected coincidence boundaries using the above equation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
39
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(39 citation statements)
references
References 4 publications
0
39
0
Order By: Relevance
“…Fig. 6 of Miyazawa et al (1996) as an illustration]. Recent experimental study (Gertsman & Bruemmer, 2001) has shown that, while AE3 boundaries are resistant to intergranular stress corrosion cracking in many practically important materials, AE9 boundaries are not.…”
Section: Figurementioning
confidence: 99%
See 3 more Smart Citations
“…Fig. 6 of Miyazawa et al (1996) as an illustration]. Recent experimental study (Gertsman & Bruemmer, 2001) has shown that, while AE3 boundaries are resistant to intergranular stress corrosion cracking in many practically important materials, AE9 boundaries are not.…”
Section: Figurementioning
confidence: 99%
“…A hypothetical polycrystal built of Kelvin's tetrakaidecahedra presented in Fig. 6 of Miyazawa et al (1996) have only four different crystal orientations and contains only the quadruple points of the type we have just considered. In that case, AE multi 27 for the whole polycrystal.…”
Section: Figurementioning
confidence: 99%
See 2 more Smart Citations
“…Random bond percolation, however, cannot be simply applied to twin-induced GBE because the GBCD produced by twin-induced GBE is under crystallographic constraints at triple junctions according to the S-product rule. 46) Schuh et al 35) showed that as compared with randomly assembled networks, about 50-75 % more resistant boundaries will be required to fragment the susceptible grain boundaries in 2-D GBCD when the Sproduct rule is adapted to the simulation, which accepts the 2-D percolation threshold of 70 % CSL frequency in 304 stainless steel (Fig. 7).…”
Section: Percolation Of Random Boundaries In Gbemmentioning
confidence: 99%